Poverty Eradication and Access to Quality Education in Nigeria: Moving Targets in the Twenty-First Century - RAJI, Ismail Adesina; ISIAKA, Babatunde Akanmu (International Journal of Educational Management, 2021)
Access to quality education has been the main target and goal of developed countries from time immemorial due to its capability to eradicate poverty among people and accelerate the development of nations. Nigerian governments at all levels of governance have also emulated the advanced nations in order to reduce significantly the poverty level due to the fact that Nigeria has been identified as the world poverty capitalwith40 percent of her total population or 83 million people live below the country's poverty line of 137,430 Naira($381.75) per year.The Federal Government of Nigeria introduced many programmes to alleviate the suffering of its citizens such as Small and Medium Enterprises, Poverty Alleviation Programme, National Poverty Eradication Programme and recently TRADERmoni, MARKETmoni, FARMERmoni, N-Power among others. It is based on this, that the paper examined poverty eradication and access to quality education in Nigeria: Moving the targets in the twenty-first century.